2019
DOI: 10.1063/1.5091933
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical design of coupled high contrast grating (CHCG) waveguides to enhance CO2 light-absorption for gas sensing applications

Abstract: In this work, we present a theoretical study on using high contrast grating (HCG) designs to enhance light–gas interaction in the mid-infrared range. The optical behavior of a single layer HCG was studied under the presence of CO2 gas. Through optimizing the structure parameters, we could confine an intense electric field over the grating layer. Consequently, about 200 times of light-absorption enhancement was observed. To further improve the performance, a coupled HCG (CHCG) was proposed to introduce another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Besides the two-dimensional PhC waveguide devices, grating structures were also studied for sensing applications. For example, Hemati et al 106 reported a design of a high contrast grating (CHCG) device for carbon dioxide (CO 2 ) sensing. The authors theoretically showed that the CHCG devices could restrict much intense light energy in the structure leading to 1400× light-absorption enhancement for developing gas sensors based on infrared absorption spectroscopy.…”
Section: ■ Principles Of On-chip Optical Gas Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the two-dimensional PhC waveguide devices, grating structures were also studied for sensing applications. For example, Hemati et al 106 reported a design of a high contrast grating (CHCG) device for carbon dioxide (CO 2 ) sensing. The authors theoretically showed that the CHCG devices could restrict much intense light energy in the structure leading to 1400× light-absorption enhancement for developing gas sensors based on infrared absorption spectroscopy.…”
Section: ■ Principles Of On-chip Optical Gas Sensorsmentioning
confidence: 99%
“…Besides the total-internal-reflection waveguide and subwavelength waveguide devices, PhC waveguide devices also attract great attention in developing optical gas sensors due to their compact device footprints and excellent ability in the light confinement. ,,,,,,, On the one hand, PhC waveguide devices are used for developing gas sensors based on enhanced infrared absorption spectroscopy, ,,,,, since slow-light effects in PhC waveguide devices could result in the absorption cross-section enhancement . For example, Lai et al used a silicon PhC slot waveguide, as shown in Figure a, for methane (CH 4 ) molecules detection at 1.55 μm wavelengths.…”
Section: Materials and Structures Of On-chip Optical Gas Sensorsmentioning
confidence: 99%
“…Recently, there are various reports that highlighted the inevitability of the gas sensors at different fields of applications. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, gas sensors are extremely necessary for the early detection of gas leakage. Compared to other gas species, detection of hydrogen is highly desirable as H 2 leakage is harmful to human safety and can be flammable and explosive when mixed with air.…”
Section: Introductionmentioning
confidence: 99%